Structural Bioinformatics studies of the Zika virus non-structural protein 1 and its molecular interactions - Cuevas, Sergio Alejandro Poveda (2022)
The Flavivirus genus is a group with more than 70 virus species generally distributed in tropical zones. Over several years, flaviviruses have been representing a great public health problem, producing thousands of deaths and infections per year. The challenges to improve the diagnostic capacity and other interventions for viruses such as Zika require the comprehension of the physical interactions that occur at the molecular level. As a therapeutic target, the nonstructural protein 1 (NS1) has been a centerpiece since it is shown as an important element in the virulence and survival of the Zika virus. Using Structural Bioinformatics approaches, we aim to understand the molecular properties and mechanisms that occur at different biological interfaces of this viral protein and their relation with virulence. Employing a constant-pH Monte Carlo computational approach and classical molecular dynamics simulations, we described several physicochemical and dynamical-structural properties that have a close relationship with molecular mechanisms where NS1 is a key player. Our results contribute to a general physicochemical understanding of the macromolecular complexation and their vast role in cell biology providing evidence for possible pharmacological interventions.